2017
DOI: 10.1007/s00705-017-3233-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between southern rice black-streaked dwarf virus minor core protein P8 and a rice zinc finger transcription factor

Abstract: The fijivirus southern rice black-streaked dwarf virus (SRBSDV) causes one of the most serious viral diseases of rice in China and Vietnam. To better understand the molecular basis of SRBSDV infection, a yeast two-hybrid screen of a rice cDNA library was carried out using P8, a minor core protein of SRBSDV, as the bait. A rice Cys2His2-type zinc finger protein (OsZFP) was found to interact with SRBSDV P8. A strong interaction between SRBSDV P8 and OsZFP was then confirmed by pull-down assays, and bimolecular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Previous studies showed that zinc finger proteins not only have transcriptional regulatory activities but also can interact with other proteins to regulate protein activity, thus regulating plant growth and disease resistance. Rice OsZFP can directly recognize P8 protein of SRBSDV and regulate rice resistance to SRBSDV [ 35 ]. OsZFP213 interacts with OsMAPK3 to enhance the ability of scavenging ROS and synergistically regulate the salt tolerance of rice [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that zinc finger proteins not only have transcriptional regulatory activities but also can interact with other proteins to regulate protein activity, thus regulating plant growth and disease resistance. Rice OsZFP can directly recognize P8 protein of SRBSDV and regulate rice resistance to SRBSDV [ 35 ]. OsZFP213 interacts with OsMAPK3 to enhance the ability of scavenging ROS and synergistically regulate the salt tolerance of rice [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has been implicated that zinc finger proteins also participate in biotic response in rice ( Figure 4B ). For example, a rice C2H2 zinc finger protein OsZFP was found to interact with southern rice black-streaked dwarf virus (SRBSDV) protein P8, a minor core protein of SRBSDV, which may play an important role in fijiviral infection and symptom development (Li, J. et al, 2017 ), implying that P8 may execute the infection by interfering with the host OsZFP . LSD1-related proteins in Arabidopsis are well known as remarkable disease-defensed zinc finger proteins.…”
Section: Impact On Agronomic Traitsmentioning
confidence: 99%
“…Phytophthora nicotianae biomass was considerably higher in NbCZF1-silenced plants compared to potato virus X control plants [ 19 ]. OsZFP interacts with southern rice black-streaked dwarf virus (SRBSDV) P8 and is crucial for the infection of the fijivirus and the emergence of symptoms [ 20 ].…”
Section: Introductionmentioning
confidence: 99%